Stative verbs and French Verb-Noun compounds: a discreet preference - Florence Villoing (Lexique, 2018)
This paper deals with French nominal Verb-Noun compounds formed on stative verb bases. We assume that word-formation schemas have access to the aspectual and argumental properties of the base verbs and impose fine-grained restrictions on their input. Contrary to what is usually claimed, the study argues that Verb-Noun compounding in French (and probably in other Romance languages) is compatible not only with dynamic verbs but also with stative ones that construct Verb-Noun compounds of high-frequency. These stative verbs are ambiguous between two readings, and verbs can have either a stative or a dynamic structure. Verb-Noun compounding generally prefers the stative verb that systematically corresponds to the class of “pure” stative (that is to say, Kimian-states). The study establishes a link between the aspectual values of the base-verb and the interpretation of VN compounds: VNs on stative base-verbs never form Agent and Instrument nominals but only Experiencer, Means or Location nominals. The inverse prediction also holds: VNs based on the dynamic agentive construction of ambiguous verbs can be interpreted as Agent or Instrument nominals but not as Experiencer or Means nominals.